Streptococcal Cysteine Protease-Mediated Cleavage of Desmogleins Is Involved in the Pathogenesis of Cutaneous Infection - Sumitomo, Tomoko; Mori, Yasushi; Nakamura, Yuumi; Honda-Ogawa, Mariko; Nakagawa, Seitaro; Yamaguchi, Masaya; Matsue, Hiroyuki; Terao, Yutaka; Nakata, Masanobu; Kawabata, Shigetada (Frontiers in Cellular and Infection Microbiology, 2018)
Streptococcus pyogenes is responsible for a wide variety of cutaneous infections ranging from superficial impetigo to fulminant invasive necrotizing fasciitis. Dysfunction of desmosomes is associated with the pathogenesis of cutaneous diseases. We identified streptococcal pyrogenic exotoxin B (SpeB) as a proteolytic factor that cleaves the extracellular domains of desmoglein 1 and 3. In an epicutaneous infection model, lesional skin infected with an speB deletion mutant were significantly smaller as compared to those caused by the wild-type strain. Furthermore, immunohistological analysis indicated cleavage of desmogleins that developed around the invasion site of the wild-type strain. In contrast, the speB mutant was preferentially found on the epidermis surface layer. Taken together, our findings provide evidence that SpeB-mediated degradation of desmosomes has a pathogenic role in development of S. pyogenes cutaneous infection.